ISLAMIC BRANDING AND MARKETING: AN INSIGHT OF CONSUMER PERCEPTION IN MAKASSAR, INDONESIA - Sabbar Dahham Sabbar; Muslimin H. Kara; Shahid Bashier; Salmah Said (International Conference on Social and Islamic Studies, 2021)
The purpose of this study is to analyze and investigate whether there is a gap between theperceptions of consumers in Makassar, Indonesian Muslim consumers about Islamic brandingand marketing and to create a deeper understanding of the perceptions of Indonesian consumers.The research method used is a quantitative method. To answer the question, the researcher useda Likert scale. Initially the scales consisted of 5 alternatives. Starting with strongly disagree (1)then ending with strongly agree (5). Likert scale estimates imply important statisticalcalculations. Based on the results of the study, it can be concluded that Islamic brandingpositively affects consumer perception. The majority population of Makassar city is Muslimswith strong faith and culture, reflected obviously in their perception of consuming towards halalgoods and services that is provided based on Islamic teachings. Islamic brand has to emphasisthat is it a brand that holds Halal sources. Then it will bears obvious perception of Islamicbrands. Therefore Islamic brands clearly adherents whatever requirement by Sharia’ to be asreal Halal brand.